OBESITY, HYPERTENSION AND INSULIN RESISTANCE IN CHILDHOOD - A PILOT STUDY - Pastucha, Dalibor; Talafa, Viktor; Malincikova, Jana; Cihalik, Cestmir; Hyjanek, Jiri; Horakova, Dagmar; Janout, Vladimir (Biomedical papers, 2010)
Background: Obesity and arterial hypertension are a serious risk factor for insulin resistance patients leading to diabetes and other disorders. Obesity is one of the most common nutritional problems in developed countries. Actually the incidence of obesity is increasing considerably, obesity is emerging in alarming rates between the last 10 years. Obesity and hypertension beginning in childhood often precedes the hyperinsulinemic state. The metabolic syndrome is rapidly increasing in prevalence with rising childhood obesity and sedentary lifestyles worldwide. The aim of this study was to compare average levels of the homeostatic indices HOMA and QUICKI in obese children compared to healthy and hypertonic children in order to find convenient markers for insulin sensitivity in clinical pediatric practice.Methods: 49 obese children (11 girls, 38 boys), 42 children healthy (33 boys and 9 girls) and 37 hypertensive children (4 girls, 33 boys) were selected.Results: The average level of HOMA in obese children was 4.58; in healthy children 1.8 and in the group of hypertonic children the level was 2.75. The average level of QUICKI in obese children was 0.22; in healthy children 0.29 and in hypertonic children 0.28.Conclusions: The results demonstrate the possibility of insulin sensitivity assessment using these indices in pediatric practice. QUICKI has a narrower confidence interval and thus a lower variability. QUICKI an HOMA indexes are useful predominantly for epidemiological purposes, mainly for maping the scope of insulinoresistance among children.
Keywords: Obesity in children/Insulin resistance/Hypertension in children/HOMA/QUICKI